O cinema está morto. Que viva o Cinema! - Nazareth, Adriano Joaquim Carvalho Barbosa (2006)
Part I The first part of this work is sustained by three verbs: to present, to reflect and to question. Faithful to the implicit objective in the subtitle financial support for cinema education in an Art School has been developed a broad and large relationship between the various techniques of moving image registration and historical notes about cinematography with special emphasis on cinema and television. On a second moment is made a reflection on the technical and aesthetical evolution of the so-called cinematography with resulting questions raised about its future. The second part of the dissertation consists of four film objects which stand as paradigms of observation and reflection matured in the experience and contact with the realities studied and presented at the first part. Outline of the 1st and 2nd part of this work: Introduction to the phenomena moving images registration from the visualization of an object to the possibility of interpreting its registry. Brief History about the practice of writing with light, and it s technical development, until it s informative, formative and artistic usage. The development of writing with light (Photo-Graphics) and the possibility of imprisoning space and time in a given fraction of time itself. The iconography used by writing with light, as a simple and appealing expression when used as significant/identifying sign. The image , its registry and conservation. If Photography shows the real, the unchangeable, in fixed a fraction of a second in time, then cinematography recreates time providing a new sequential order. The origins of cinematography: forms of registry, forms of usage. Fiction and Documentary typology formation/information/research. The speech and language of cinematography. Brief history of cinematography, its technical, aesthetical and poetical evolution. Language used in cinematography. The film narrative in space and time, synthesizing Art in space. Techniques of registration Analogue and Digital systems. From the early days of Animation to the present. Roles of the language figures of speech and figures of thought . Rules of Animation rest, movement and action. Types of movement and framing. Guidelines of Animation. Main characteristics of Animation Characters Sound/image. Style topics content/form. The trilogy Form/Figure/End. Technical development of Animation and necessary changes for narrative. Brief reflection on some Animation products. Relation between emitter/receptor, new applied codes. Contemporary Animation and its target audience. Special Effects and its manipulators. Cinematography as a form of Art Expression. Cinema as an autonomous Art or as reproduction a synthesis of elements. Cinematography and three Arts verbal, figurative and sonic correspondences. Cinema and the diversity of information. The cinematographic signification. Characteristics of a cinematographic text. Division of superior form of communication. Fiction and its rational and irrational needs. Differentiated forms of behaviour. Cinematographic objects; summary of some authors. Show Cinema, Industry Cinema and Author Cinema compromises . Documentary: Content/form. Trajectories of non-fictional cinema. Brief historical notes on documentary. Cinematographic trends on non-fictional cinema Neo Realism Free Cinema Manifest Cinema Political Cinema Exploiting Documentary the nature of Documentary Art as Documentary Theme Exploratory Documentary. Cinema and Television. Differences and resemblances. Television Stations General and Thematic characteristics content/form. Map type/programming. Image/framing excess of information on generalist television. Audiovisuals cinema versus television. Considerations on the production of a Television program.